Fatty acids and tocochromanol patterns of some Turkish Apiaceae (Umbelliferae) plants; a chemotaxonomic approach - Bagci, Eyup (Soc Botanique France, 2007)
The plant family Apiaceae is known to produce a set of unusual fatty acids in the seed oils. The fatty acids and tocochromanols contents of some species of Prangos, Ferulago, Heracleum, Conium and Malabaila from Apiaceae are determined and analysed by GC, GC-MS and HPLC. Some of the studied species are endemic to Turkey. Petroselinic acid (18:1 Delta 6c) is the predominant constituent and consisted of more than half of the oil. Linoleic acid is the second highest fatty acid component. There is very little variation among species in the other fatty acids. In contrast, the tocopherol compositions of the seed oils differ. Tocotrienol contents of the species (except Malabaila pastinicifolia and Ferulago pauciradiata) are found to be higher than the tocopherols, particularly in view of gamma and delta tocotrienols. The relative concentrations of petroselinic acids and tocochromanols in seed oils of Apiaceae show chemotaxonomic and phylogenetic relationships. These acids have also potential as oleochemical raw materials.
Keywords: Apiaceae; chemotaxonomy; fatty acid; petroselinic acid; tocochromanols